Biogeographical Importance of the Livingstone Mountains in Southern Tanzania: Comparative Genetic Structure of Small Non-volant Mammals - Cuypers, Laura N.; Sabuni, Christopher; Šumbera, Radim; Aghová, Tatiana; Lišková, Edita; Leirs, Herwig; Baird, Stuart J. E.; Goüy de Bellocq, Joëlle; Bryja, Josef (Frontiers in Ecology and Evolution, 2022)
The Livingstone Mountains (LM; also known as the Kipengere Range) found in south-western Tanzania at the northern end of Lake Nyasa are an important region for understanding the biogeography of Eastern Africa. The two branches of the East African Rift Valley meet here and the mountains might represent stepping stones for colonization and migration between different parts of the Eastern Afromontane Biodiversity Hotspot (especially the link between the Eastern Arc Mountains, EAM, and the Southern Rift Mountains, SRM), as well as an efficient barrier to gene flow for taxa living in drier savannahs in lower elevations. Here we combine new mitochondrial sequence data from 610 recently sampled rodents and shrews with available georeferenced genetic data (3538 specimens) from southern Tanzania, northern Malawi/Zambia and northern Mozambique and compare the spatial genetic structure among different taxa. There is no universal phylogeographic pattern in taxa preferring humid montane habitats. For some of them, the Makambako Gap acts as a barrier between the SRM and the EAM, but other taxa can bridge this gap. Barriers within the EAM (frequently) and within the SRM (sometimes) appear more important. The Rukwa rift between the SRM and the ARM is an important barrier that perhaps can only be crossed by taxa that are not that strictly tied to humid montane environments. For mammals living in lower-elevation savannah-like habitats, the LM can act as a strict barrier to gene flow, and together with the Ufipa Plateau, Lake Nyasa and the EAM create a very similar phylogeographic pattern with three recognizable genetic groups in most savannah-dwellers. The Livingstone Mountains thus appear to be one of the most important biogeographic crossroads in Eastern Africa.